Effect of photovoltaic (PV) module degradation rate on the greenhouse gas emissions: a life-cycle assessment / Atiqah Hamizah Mohd Nordin ...[et al.] - Mohd Nordin, Atiqah Hamizah; Sulaiman, Shahril Irwan; Shaari, Sulaiman; Mustapa, Rijalul Fahmi (Universiti Teknologi MARA, 2021)
In this paper, a life-cycle assessment (LCA) is carried out to evaluate the greenhouse gas emissions of the photovoltaic (PV) system, focusing on the effect of the PV module degradation rate throughout the system's lifetime. The LCA is done on monocrystalline silicon PV module technology using actual data from manufacturers' datasheets. In this study, three different manufacturers under three scenarios are done, which involves the inclusion and exclusion of the degradation factor: i) Scenario A - PV module degradation is considered with a PR of 0.75, ii) Scenario B - PV module degradation is considered and the PR is calculated based on each PV module's temperature coefficient and other de-rating factors, iii) Scenario C - PV module degradation is ignored. Using the Intergovernmental Panel of Climate Change (IPCC 2013) impact assessment method, the results show that the greenhouse gas (GHG) emissions rate ranges from 66.05 to 79.25 g CO2-eq/kWh depending on the scenarios presented. The results also suggest that a lower degradation rate reduces the environmental burden of the PV system.